Solving real world problems with applied mathematics.
What do tsunamis, the blood flowing through our veins, nuclear fusion, earthquakes, aircraft noise and clean energy have in common? According to the EU-funded STIMULUS project, they all share a common mathematical formulation as nonlinear systems of hyperbolic conservation laws.